(untitled) (Jurnal EurekaMatika, 2018)
Let G=(G,C) be a cyclically ordered group and A,B be subgroups of G such that some conditions are satisfied. Based on these assumptions, defined a lexicographic product decomposition on G with factors A and B, denoted by G = AB. Furthermore, a lexicographic product decomposition of the cyclically ordered group will have a refinement. Let G and H be an isomorphic dc-group, expressed as the finite lexicographic product decomposition of each of its subgroups, then it will always have isomorphic refinements. ABSTRAK Misalkan G = (G,C) adalah cyclically ordered group dan A,B adalah subgrup dari G sedemikian sehingga memenuhi beberapa kondisi. Berdasarkan asumsi tersebut, didefinisikan dekomposisi produk leksikografik pada G dengan faktor A dan B, dinotasikan dengan G = A?B. Lebih lanjut, suatu dekomposisi produk leksikografik pada cyclically ordered group akan memiliki refinement. Misalkan G dan H adalah dc-group yang isomorfik, yang dinyatakan sebagai dekomposisi produk leksikografik berhingga dari masing-masing subgrupnya, maka akan selalu memiliki isomorphic refinements.